Pemberdayaan UMKM Dalam Meningkatkan Profitabilitas Di Lingkungan Amal Usaha Muhammadiyah Di Medan - Nasution, Salman; Mujiatun, Siti; Fanreza, Robie; Nurzannah; Munasip, Adi (ABDI SABHA (Jurnal Pengabdian kepada Masyarakat), 2024)
How to increase the profits (profitability) for MSMEs (Micro, Small and Medium Enterprises) is to facilitate the economic empowerment. The aim of implementing service to MSMEs in the Muhammadiyah area in Medan is to find the various problems of MSMEs which only gain profits when Muhammadiyah enterprises activities in educational schools. MSMEs tend to stagnate in terms of their profit and product levels, in addition to the minimal role of Muhammadiyah leadership in providing moral and material support (financing). The results of dedication to empowering MSMEs in the Muhammadiyah area of Medan include creating strategies including collaboration between MSMEs in the Muhammadiyah enterprises in Medan by selling products to Muhammadiyah members and sympathizers. Apart from that, MSME product innovation is really needed in order to provide interest to (potential) consumers not only in the market segment within the Muhammadiyah area, but also outdoor Muhammadiyah area. The final solution in this empowerment is the concern of Muhammadiyah enterprises leaders and Muhammadiyah leadership as Muhammadiyah enterprises management towards MSMEs to provide moral and material support (providing access to financing) in the Muhammadiyah economic movement